Detection of Cl- binding to band 3 by double-quantum-filtered 35Cl nuclear magnetic resonance. - Liu, D (1996)
We have applied double-quantum-filtered (DQF) NMR of 35Cl to study binding of Cl- to external sites on intact red blood cells, including the outward-facing anion transport sites of band 3, an integral membrane protein. A DQF 35Cl NMR signal was observed in cell suspensions containing 150 mM KCl, but the DQF signal can be totally eliminated by adding 500 microM 4,4'-dinitrostilbene-2,2'-disulfonate (DNDS), an inhibitor that interferes with Cl- binding to the band 3 transport site. Therefore, it seems that only the binding of Cl- to transport sites of band 3 can give rise to a 35Cl DQF signal from red blood cell suspensions. In accordance with this concept, analysis of the single quantum free induction decay (FID) revealed that signals from buffer and DNDS-treated cells were fitted with a single exponential function, whereas the FID signals of untreated control cells were biexponential. The DQF signal remained after the cells were treated with eosin-5-maleimide (EM), a noncompetitive inhibitor of chloride exchange. This result supports previous reports that EM does not block the external chloride binding site. The band 3-dependent DQF signal is shown to be caused at least in part by nonisotropic motions of Cl- in the transport site, resulting in incompletely averaged quadrupolar couplings.